MTF Estimation for IR Optical Systems - Ahmad, Ahmad K; Mohammed, Hassan H; Khorsheed, Suha M (Al-Nahrain Journal of Science, 2013)
This paper deals with difficulty of estimating the modulation transfer function (MTF) of thermal IR (infrared) images, which almost content some of distortion. The distortion makes the features of the image to be embedded and cannot observe. This necessitates adopting a parameter work out through the frequency domain in order to appear the features needed to describe the image well. MTF is the most descriptive parameter used to evaluate both the contrast and resolution of the image, but it is characterized by its difficult estimation. The present work adopted two methods; spatial based method and frequency based method. The results of the two adopted methods were very similar. In order to ensure the correct results, the results of the two methods are compared with that extracted from Zemax software. The comparison shows great similarity in between, which indicates the correct path of the computation and accurate description of the proposed methods.